God and Creation - Reed, Rodney L.; Ngaruiya, David K. (Langham Global Library, 2019)
This collection of essays – the product of the 8th annual conference of the Africa Society of Evangelical Theology – wrestles with the topics of God and creation from distinctly African perspectives. Touching on topics from environmentalism, to ethnic conflict, to childlessness, the contributors present a powerful and timely reflection on the nature of God as creator and the implications of that identity on our relationship with the divine, with the earth, and with each other.
Paid